Surface modification of Ti-30Ta alloy by electrospun PCL deposition - Wada, Cristiane Mayumi [UNESP]; Rangel, Andrï¿½ Luiz Reis [UNESP]; de Souza, Marisa Aparecida [UNESP]; Almeida, Rosemeire dos Santos; D’ï¿½vila, Marcos Akira; Rosifini Alves Claro, Ana Paula [UNESP]; Rosifini Alves Rezende, Maria Cristina [UNESP] (My University, 2016)
In this study, PCL electrospun fibers were deposited on the Ti-30Ta alloy for change the surface properties. Experimental Ti-30Ta alloy was obtained by melting titanium and tantalum in arc melting furnace with argon atmosphere. Ingots were homogenized and bars with 10 mm of diameter were obtained in rotative swagging. PCL fibers were deposited on disks of the alloy by electrospinning. Plasma treatment was carried out for change PCL electrospun superficial energy by using stainless steel plasma reactor. Samples were immersed in mineralization solution for apatite growth. Surfaces were evaluated by using SEM, X-rays diffraction and contact angle. Samples exhibited hydrophilic behavior after plasma treatment and mineralization. Results are very interesting for biomedical applications.
Keywords: Alkaline treatment; Electrospinning PCL; Mineralization; Plasma treatment; Ti-30Ta alloy